Harvest time impacts the fatty acid compositions, phenolic compounds and sensory attributes of Frantoio and Manzanilla olive oil - Alowaiesh, B.; Singh, Zora; Fang, Zhongxiang; Kailis, S. (Elsevier, 2018)
The effect of harvest time at different ripening stages of fruit influences quality of olive oil. Therefore, the current investigations were conducted during 2013 and 2014 to explore the effects of five different harvesting times (mid- and late-April, mid- and late-May and mid-June) on chemical and sensory attributes of Frantoio and Manzanilla olive oil. The fatty acids of olive oil showed significant increase (palmitic acid, stearic acid, linoleic acid and PUFA) or decrease (oleic acid, MUFA, and MUFA:PUFA ratio) with the delay in harvesting irrespective of the cultivars. A significant gradual decrease was noted in major polyphenol compounds from the first to the fifth harvest. The concentration of phenolic compounds was comparatively higher in the fruit harvested in 2014. The sensory attributes of oil in both cultivars deteriorated with the delay of harvesting, with water stress possibly influencing the bitterness of the fruit in 2014. The harvesting in early part of winter under Mediterranean climate produced olive oil with better chemical and sensory attributes. Higher concentrations of phenolic compounds were observed in 2014 with less rainfall; however, the trend of declining concentration on phenolics from the first to the fifth harvest was comparatively prominent in 2014 than 2013.